2016
DOI: 10.2147/ott.s113307
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of systemic and local inflammation in patients with laryngeal squamous cell carcinoma

Abstract: BackgroundCancer-related systemic inflammation has been demonstrated to be associated with poor outcome in multiple types of cancers. Meanwhile, the local inflammation, which is characterized by dense intratumoral immune infiltrate, is a favorable predictor of survival outcome.PurposeTo evaluate the role of systemic and local inflammation in predicting outcome in patients with laryngeal squamous cell carcinoma.Patients and methodsIn this retrospective study, 120 patients who had undergone postoperative radioth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(111 citation statements)
references
References 39 publications
1
110
0
Order By: Relevance
“…Therefore, meta-analyses were conducted with a random effect model, using Comprehensive Meta-Analysis version 2 (Biostat, Englewood, NJ). However, only 4 studies 38,42,44,46 were subjected to subgroup analyses for disease sites because the other studies reported the HRs of patients with different affected sites together. Most of the included studies dichotomized patients into 2 groups according to the platelet count or PLR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, meta-analyses were conducted with a random effect model, using Comprehensive Meta-Analysis version 2 (Biostat, Englewood, NJ). However, only 4 studies 38,42,44,46 were subjected to subgroup analyses for disease sites because the other studies reported the HRs of patients with different affected sites together. Most of the included studies dichotomized patients into 2 groups according to the platelet count or PLR.…”
Section: Discussionmentioning
confidence: 99%
“…The HRs for DSS were reported in 3 studies and ranged from 0.95 to 1.62; none were statistically significant 37,39,51 ( Figure 2B). Table 2 37,38,[41][42][43][44][45][46]51 shows the characteristics of the included studies for PLR analysis. The pooled HR for DSS was 1.13 (95% CI 0.90-1.43), and the result was not statistically significant.…”
Section: Platelet Countmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar favorable findings were seen with increased intra-tumoral or stromal CD8 + cells [240], while increased numbers of FOXP3 + T regs may have detrimental effects oral cavity squamous cell carcinoma outcome [241]. Vassilakopoulou et al and Wang et al applied the consensus TILs scoring guidelines from the International Immuno-Oncology Biomarkers Working Group [1] to laryngeal squamous cell carcinoma, and both studies found that the sTILs score was an independent prognostic factor for disease free and overall survival [242,243]. …”
Section: Tils In Head and Neck Squamous Cell Carcinomamentioning
confidence: 99%